Предмет: Алгебра, автор: DariaMatt

1-sin^4 а- cos^4 а/ cos^4a

Ответы

Автор ответа: Матов
0

(1- sin^4a-cos^4a)/cos^4a   =

(4-3-cos4a/4) /cos^4a =

(1-cos4a)/4cos^4a =

 (8cos^2a- 8 cos^4a)/4cos^4a =  (2/cos^2a) -2=(2-2cos^2a)/cos^2a

 

 

Автор ответа: Аноним
0

frac{1-sin^{4}a- cos^{4}a}{cos^{4}a} = frac{(1-sin^{2}a) (1+sin^{2}a) - cos^{4}a}{cos^{4}a}=\ frac{(1+sin^{2}a)cos^{2}a- cos^{4}a}{cos^{4}a} =\ frac{cos^{2}a(1+sin^{2}a- cos^{2}a)}{cos^{4}a} =\ frac{1+ sin^{2} a-cos^{2}a}{cos^{2}a}=\ frac{sin^{2}a+cos^{2}a+sin^{2}a-cos^{2}a}{cos^{2}a}=\ frac{2sin^{2}a}{cos^{2}a}=\ 2tg^{2}a

Похожие вопросы
Предмет: Литература, автор: JuliaSWS